The Detrimental Effects of Ineffective Foreign Policies on Democracy - Thapa, Santa Bahadur (Darul Yasin Al Sys, 2025)
This paper examines the complex interplay of foreign policy and democracy, detailing how one nation's foreign policy can profoundly influence its democratic base. While shrewd foreign policy can reinforce democratic governance, economic growth, and international cooperation, misplaced or incompetent foreign policy will undermine trust in the public, destabilize institutions, and lay the groundwork for authoritarianism. This paper reviews how failed foreign policies underlie the crisis in democracy, engaging with literature from various regions. Mistakes in foreign policy can lead to serious repercussions, including economic decline, social unrest, loss of a nation’s reputation and credibility, and alienation of public trust. Building on its analysis of the correlation between foreign policy miscalculations and democratic decay, the paper uses the specific examples of US intervention in Iraq, Russian aggression toward Ukraine, Saudi engagement in Yemen, and Chinese adventurism in the Indo-Pacific to illustrate how elite foreign policy failures have ushered in democratic backsliding and a decline of democratic norms and institutions throughout their societies. The paper concludes that responsible and effective foreign policy is based on democratic values, respect for human rights, and international cooperation. These policies allow nations to create democracy at home and promote a more peaceful, prosperous world.